Adaptations to unaccustomed resistance training for women in physically demanding occupations - McGuire, Stephen (Cranfield University, 2020)
Improvements in maximal strength may reduce injury risk and improve occupational performance. Women’s naturally lower muscular strength compared to men, can be offset through resistance training (RT), but research into its implementation has been limited. Therefore, the time-course of muscular adaptations is of interest, with evidence suggesting adaptations in size and strength are detectable as early as 3-4 weeks, concomitant with an attenuation of RT induced muscle damage. This evidence offers a reduction in the time commitment of RT that may enhance readiness for physically demanding activity, but functional adaptations have yet to be explored. The purpose of this thesis is to explore measurement techniques, moderators of baseline variation and responses to unaccustomed heavy-load RT in civilian women representative of individuals entering physically demanding occupations. Specifically, high reliability and acceptable validity as a measure of maximal strength was established for the isometric mid-thigh pull, now a UK Armed Forces entrance test, in non-athlete females. Next, the influence of physical characteristics, previous sporting activity, and single nucleotide polymorphisms on variation in strength was assessed. The ongoing final study aims to assess the efficacy of a 4-week heavy compound RT program on improving performance and biochemical adaptations.
Keywords: 'Resistance training'; 'Women'; 'Physical demands'; 'DSDS19'; 'DSDS19 3MT'; 'Exercise Physiology'